Content area reading : literacy and learning across the curriculum - Vacca, Richard T.; Vacca, Jo Anne L. (Boston : Allyn and Bacon, 2002)
This text is designed to be an active learning tool, complete with real-world examples and practices from which students can work. The Seventh Edition has a reorganized format to reflect the text's exploration of content literacy. This organization reflects an integrative approach to literacy. Content area reading has grown into a reflective exploration of content literacy the ability to use reading, writing, speaking, and listening processes to learn subject matter across the curriculum. This text's organization reflects this interpretative approach to literacy.
Includes bibliographical references (p. 443-457) and index.
Keywords: Content area reading